Principal Management to Improve Elementary School Teacher Motivation - Sari, Rianti Garvita; Komara, Endang (Papanda Publisher, 2025)
Principal management plays a crucial role in enhancing teacher motivation, which significantly influences instructional quality and student outcomes. However, limited research has systematically examined the specific mechanisms through which principal management practices affect teacher motivation in elementary school contexts. This qualitative case study was conducted at two elementary schools in West Java: SDN Subangjaya 2 (Sukabumi City) and SDN 191 Babakan Surabaya (Bandung City). Data collection employed participatory observation, in-depth semi-structured interviews with principals and teachers, and comprehensive documentation analysis. Data were analyzed using Miles and Huberman's interactive model, guided by Deming's PDCA management theory and Maslow's hierarchy of needs theory. The study revealed significant variations in management practices between the two schools across four key dimensions: planning, implementation, supervision, and follow-up activities. SDN 191 Babakan Surabaya demonstrated systematic management approaches with structured supervision, regular feedback, inclusive decision-making, and consistent recognition systems. In contrast, SDN Subangjaya 2 showed limited utilization of collaborative facilities, informal supervision, and inadequate performance recognition, leading to teacher dissatisfaction and desire for transfer. Effective principal management requires systematic implementation of the PDCA cycle integrated with understanding of teachers' motivational needs. The successful practices at SDN 191 created conditions addressing teachers' professional security, collaboration needs, appreciation, and growth opportunities simultaneously, demonstrating that implementation quality determines motivational outcomes rather than program design alone. These findings have important implications for principal training and educational policy development in elementary education settings.